The Professıonal Autonomıes Of Nurses Workıng In The State Of Nazilli Hospıtal And The Affectıng Factors - Sebahattin Yetim; Kerime Derya Beydağ (Association of Nurse Managers, 2015)
INTRODUCTION: This study has been carried out as descriptive research with the object of determining professional autonomy of nurses working at Nazilli Public Hospital and factors affecting it. METHODS: The study was conducted between 03.06.2013 and 19.08.2013 at Nazilli Public Hospital. 194 nurses working at Nazilli Public Hospital constituted the research population, it was aimed to reach out all population without choosing sample however 184 nurses (%94,8) formed the sample group. Data were developed by demographic data form and Shutzenhofer (1992), validity and reliability for our country were achieved by 'Nursery Activity Scale' done by Saraçoğlu (2010). Research data were evaluated using standard deviation, mean, frequency distribution, Kolmogorov Smirnov test, oneway ANOVA test and student-t test. RESULTS: Average score of the nurses according to Nursery Activity Scale (NAS) is 158,36+-29,72 and autonomy level of them has been considered to be intermediate (between 121 and 180). DISCUSSION AND CONCLUSION: No statistically significant different has been found between their average NAS score and clinics the nurses work, their education levels, status and filling their roles in parallel with their professional goals (p>0,05).